2015
DOI: 10.1007/5584_2015_193
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of FCGR2A, FCGR2C, and FCGR3B Genes in the Pathogenesis of Sarcoidosis

Abstract: We have previously presented evidence that the polymorphism of the FCGR3A gene, encoding the receptor for Fc fragment of immunoglobulin G IIIa (FcγRIIIa) plays a role in the enhancement of circulating immune complexes (CIs) with the occurrence of Mycobacterium tuberculosis heat shock proteins in patients with sarcoidosis (SA). The immunocomplexemia might be caused by decreased affinity of CIs to Fcγ receptors, with the subsequently decreased receptor clearance by immune cells. In the present study we examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…This is in agreement with previously shown elevated presence of both FcγR class II and III receptors on monocytes in peripheral blood of our patients with sarcoidosis [10]. Moreover, in our previous study we have reported an increase in frequency of functional 57Q allele and 57XQ genotype of FCGR2C gene in Stage III and IV of SA [12]. In contrast to a 57X allele, creating a stop codon, presence of 57Q allele of FCGR2C results in production of a full-length, functional FcγRIIc receptor on a surface of immune cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with previously shown elevated presence of both FcγR class II and III receptors on monocytes in peripheral blood of our patients with sarcoidosis [10]. Moreover, in our previous study we have reported an increase in frequency of functional 57Q allele and 57XQ genotype of FCGR2C gene in Stage III and IV of SA [12]. In contrast to a 57X allele, creating a stop codon, presence of 57Q allele of FCGR2C results in production of a full-length, functional FcγRIIc receptor on a surface of immune cells.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, since FcγRIIIb is bound to a cell membrane only with a glycosylphosphatidylinositol anchor, it needs to colocalise with and signal through other receptors, such as FcγRIIa, in order to trigger neutrophils’ phagocytosis, oxidative burst and formation of neutrophil extracellular traps in tissues, a proinflammatory process that is linked to autoimmunity [35]. In our previous study, we have shown increased frequency of 131HH genotype of FCGR2A gene, encoding FcγRIIa, in more advanced stages of SA versus initial Stages I/II [12]. The possession of 131HH genotype results in higher affinity of FcγRIIa receptor to immune complexes and initiation of augmented (auto)immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have described d a connection between the presence of Mycobacterium tuberculosis heat-shock proteins in sarcoidosis patients and polymorphisms of genes encoding for FC receptor γ. This suggests that reduced clearance of TB immune complex may be relevant in the pathogenesis of sarcoidosis [ 15 ]. Familial clusters have been described, but are relatively uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…Another genetic polymorphism, FCGR2A and FCGR2C, has been identified as a potential tool in predicting clinical course of sarcoidosis. 10…”
Section: Presence/absence Of Extra-cardiac Sarcoidosismentioning
confidence: 99%